Deconstructing delirium in the post anaesthesia care unit - Banerji, Antara; Sleigh, Jamie W.; Voss, Logan J.; Garcia, Paul S.; Gaskell, Amy L. (Frontiers in Aging Neuroscience, 2022)
The course of neuro-cognitive recovery following anaesthesia and surgery is distinctive and poorly understood. Our objective was to understand patterns of neuro-cognitive recovery of the domains routinely assessed for delirium diagnosis in the post anaesthesia care unit (PACU) and to relate them to the cognitive recovery patterns observed in a study on healthy volunteers by Mashour et al; thereby aiding in the identification of pathological (high risk) patterns of recovery in the PACU. We also compared which of the currently available tests (3D-CAM, CAM-ICU, NuDESC) is the best to use PACU.This was a post-hoc secondary analysis of data from the Alpha Max study which involved 200 patients aged over 65, scheduled for elective surgery under general anaesthesia lasting more than 2 hours. These patients were assessed for delirium at 30 minutes following arrival in the PACU, if they were adequately arousable (Richmond Agitation Sedation Score ≥ −2). All tests for delirium diagnosis (3D-CAM, CAM-ICU, NuDESC) and the sub-domains assessed were compared to understand temporal recovery of neurocognitive domains. This data was also analysed to determine the best predictor of PACU delirium. We found the incidence of PACU delirium was 35%(3D-CAM).Individual cognitive domains were affected differently. Few individuals had vigilance deficits (6.5%,n=10 CAM-ICU) or disorganized thinking(19% CAM-ICU,27.5% 3D-CAM), in contrast attention deficits were common (72%, n=144) and most of these patients (89.5%,n=129) were not sedated (RASS≥ −2). CAM-ICU (27%) and NuDESC(52.8%) detected fewer cases of PACU delirium compared to 3D-CAM. In conclusion, return of neurocognitive function is a stepwise process; Vigilance and Disorganized Thinking are the earliest cognitive functions to return to baseline and lingering deficits in these domains could indicate an abnormal cognitive recovery. Attention deficits are relatively common at 30 minutes in the PACU even in individuals who appear to be awake. The 3D CAM is a robust test to check for delirium in the PACU. Abbreviations: 3D-CAM (3-minute Confusion Assessment Method),CAM-ICU (Confusion Assessment Method for the Intensive Care Unit), NuDESC (Nursing Delirium Screening Scale)